INDICATION OF GRAIN ENLARGEMENT IN DRY GRINDING PROCESS USING A ROD MILL, OBSERVED AT INCREASED MILLING TIME - Sedarta Sedarta; Lismawaty Lismawaty; Mahyuzar Masri (Indonesian Mining Journal, 2015)
The aim of the study is to determine whether size distribution and grain properties of the milling product can be controlled by rod size, milling time or a combination of both. Milling experiments had been carried out using rod of 9.8, 23.8, and 46.0 cm respectively as well as milling time of 30, 60, 210, 360 and 600 minutes. Grain properties were studied by sieve analysis and binocular microscope. The entire rod sizes and 30-minutes mill- ing time yielded grain enlargement as a result of van der Waals forces among colliding particles with the help of dampness as a binding media. The longer the milling time, the more coalesce the grains. It is also known that the smaller the particles, the lesser the particle density but the brighter the grain appearance. For all combina- tions, grain enlargement took place within size of -60 +100# showing the highest weight proportion in the period of 286.54 minutes.